AI-driven precision agriculture for enteric methane mitigation: cross-farm validation with an essential oil-based feed additive - Yaniv Altshuler; Yaniv Altshuler; Tzruya Calvao Chebach; Shalom Cohen; Joao Gatica (Frontiers in Sustainable Food Systems)
Ruminant livestock production depends on microorganisms to ferment forages into valuable dairy and meat products. However, this process also generates enteric methane emissions, a significant contributor to anthropogenic greenhouse gases. Despite various strategies aimed at reducing methane emissions, success has been limited. In previous work, we developed an AI-driven model based on deep microbiome sequencing, which predicts the effect of feed additives on methane emissions. The model uses sequenced rumen samples from a given herd to construct microbiome networks to identify biomarkers associated with feed additive effectiveness in the reduction of methane emissions. In this study, we validated the model supplying a commercial methane-mitigating feed additive and performing hundreds of in-situ methane measurements across several commercial dairy farms. The results highlight the model’s robustness and precision, demonstrating its effectiveness in predicting enteric methane reductions and enhancing feed additive performance. Additionally, the model serves as a critical tool for data-driven decision-making, playing a pivotal role in advancing precision agriculture practices.